Clinical Value and Potential Mechanism of miRNA-33a-5p in Lung Squamous Cell Carcinoma - Xiang-Ming Wang; Shang-Wei Chen; Gang Chen; Hua-Fu Zhou; Ting-Qing Gan; Jing-Jing Zeng; Zu-Yun Li (Analytical Cellular Pathology)
This study is aimed at thoroughly exploring the expression status, clinical significance, and underlying molecular mechanism of miRNA-33a-5p in lung squamous cell carcinoma (LUSC). Here, we detected miRNA-33a-5p in 20 samples from patients with LUSCs and 20 matching non-LUSC specimens by in-house quantitative real-time PCR (RT-qPCR). Relationship between miRNA-33a-5p expression and clinicopathological traits was investigated from materials derived from miRNA sequencing and miRNA microarrays. A pool standard mean difference (SMD) and summary receiver operating characteristic curves (SROC) were calculated to evaluate the integrated expression value of miRNA-33a-5p in LUSC. Twelve online platforms were applied to select potential target genes of miRNA-33a-5p. The differentially expressed genes (DEGs) of LUSC and the candidate target genes of miRNA-33a-5p were overlapped to acquire a set of specific genes for further analyses of the Kyoto Encyclopedia of Genes and Genomes (KEGG), Gene Ontology (GO), and protein–protein interaction (PPI) network. miRNA-33a-5p overexpressed in LUSC was supported by 706 LUSC and 261 non-LUSC samples gathering from RT-qPCR, miRNA-seq, and public miRNA microarrays. The pooled SMD was 0.56 (95% CI: -0.01-1.05), and the area under the curve (AUC) of the SROC was 0.78 (95% CI: 0.74-0.82). A total of 240 genes were identified as potential target genes of miRNA-33a-5p for functional enrichment analyses; the results suggested that these target genes may participate in several vital biological processes that promote the proliferation and progression of LUSC. miRNA-33a-5p may play an essential role in the occurrence and development of LUSC by targeting hub genes (ETS1, EDNRB, CYR61, and LRRK2) derived from the PPI network. In summary, our results indicated that miRNA-33a-5p may contribute as a prospective therapeutic target in LUSC.